KETERAMPILAN DASAR MENGELOLA KELAS DALAM MENINGKATKAN HASIL BELAJAR SISWA MADRASAH ALIYAH MUJAHIDIN PONTIANAK - (F55208018), Sutrisno; Ibrahim, M. Yusuf; ., Rustiyarso (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
The title of this thesis is, analysis of the basic skills of classroom management by teachers of sociology in improving student learning outcomes in class XI Madrasyah Aliyah Mujahidin Pontianak with the problem of